End-to-end QoS architecture for 4G scenarios - Sargento, Susana (2005)
This paper describes the QoS architecture and the corresponding QoS signalling protocols to be developed inside the IST project Daidalos. We address the main results achieved in terms of the definition of the QoS components and its interfaces, the description of the application and network services, definition of the signalling scenarios for the integration of the QoS signalling with the application signalling and with mobility approaches, and specification of the intra- and inter- domain QoS control approaches. We also describe the QoS management of the system, through the Policy–based Management System, and a Real-time Network Monitoring system able to aid in admission control with the results of active and passive measurements. All the elements, interfaces and functionalities take into account multicast services and inherent broadcast networks.